Counselors’ Mind-skills and Self-compassion during Counseling Service - Antika, Eni Rindi; Mulawarman, Mulawarman; Nusantara, Bobby Ardhian; Octasya, Tivanny; Stoic, Vip Brilliant; Bhana, Mirabai; Prabawa, Abi Fa’izzarahman (Jurnal Kajian Bimbingan dan Konseling, 2024)
The purpose of this study was to determine the level of mind skills and self-compassion of school counselors in counseling services. The research method used quantitative with a cross-sectional survey research design. The instruments used in this study were mind-skills test instruments and self-compassion scales. The test on the validity and reliability of research instruments was performed using two ways. The validity of the mind-skills test instrument uses the point biserial technique because the data was dichotomous (true or false). The validity test of the self-compassion scale was carried out with the Pearson product-moment correlation point using an error level of 5%. The reliability test value of the mind-skills test instrument was 0.836 while the self-compassion scale was 0.804. Judging from the degree of reliability scale, the two instruments are included in the degree of strong reliability. The results of this study indicate that the school counselor's level of mind skills is in the very high category (M = 32.23) and the school counselor's level of self-compassion is in the high category (M = 77.03). The data in this study can be used to design counselor competency development programs, for example, compassion training.